Citrullination of DNMT3A by PADI4 regulates its stability and controls DNA methylation. Issue 13 (23rd June 2014) - Deplus, Rachel; Denis, Hélène; Putmans, Pascale; Calonne, Emilie; Fourrez, Marie; Yamamoto, Kazuhiko; Suzuki, Akari; Fuks, François
Abstract: DNA methylation is a central epigenetic modification in mammals, with essential roles in development and disease. De novo DNA methyltransferases establish DNA methylation patterns in specific regions within the genome by mechanisms that remain poorly understood. Here we show that protein citrullination by peptidylarginine deiminase 4 (PADI4) affects the function of the DNA methyltransferase DNMT3A. We found that DNMT3A and PADI4 interact, from overexpressed as well as untransfected cells, and associate with each other's enzymatic activity. Both in vitro and in vivo, PADI4 was shown to citrullinate DNMT3A. We identified a sequence upstream of the PWWP domain of DNMT3A as its primary region citrullinated by PADI4. Increasing the PADI4 level caused the DNMT3A protein level to increase as well, provided that the PADI4 was catalytically active, and RNAi targeting PADI4 caused reduced DNMT3A levels. Accordingly, pulse-chase experiments revealed stabilization of the DNMT3A protein by catalytically active PADI4. Citrullination and increased expression of native DNMT3A by PADI4 were confirmed in PADI4-knockout MEFs. Finally, we showed that PADI4 overexpression increases DNA methyltransferase activity in a catalytic-dependent manner and use bisulfite pyrosequencing to demonstrate that PADI4 knockdown causes significant reduction of CpG methylation at the p21 promoter, a known target of DNMT3A and PADI4. Protein citrullination by PADI4 thus emerges as a novel mechanism for controlling a de novo DNA methyltransferase. Our results shed new light on how post-translational modifications might contribute to shaping the genomic CpG methylation landscape.